1980
DOI: 10.1071/ch9801993
|View full text |Cite
|
Sign up to set email alerts
|

Use of binary diffusion and second virial coefficients to predict viscosities of gaseous systems

Abstract: Accurate binary diffusion coefficients measured over the temperature range 275-323 K, together with some excellent virial coefficients in the literature, have been used to derive (m,6,8) potential parameters for the systems He-CH4, He-CF4, He-O2, Ar-O2, CH4-C2H6, CH4-C3H8 and CH4-C4H10. These parameters predict quite well the viscosities reported for these systems by Kestin and coworkers. The results indicate that binary diffusion coefficients can be used to predict viscosities more accurately than binary visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Relative deviations of experimental data and calculated values for the binary diffusion coefficient of the (CH 4 + C 3 H 8 ) system in the dilute gas phase from values calculated at the same molar densities using the CH 4 –C 3 H 8 PES of the present work, the CH 4 –CH 4 PES of ref , and the C 3 H 8 –C 3 H 8 PES of ref as a function of temperature: ●, Gotoh et al, x CH 4 = 0.5; , Arora et al, x CH 4 = 0.2, smoothed values; – · −, result for the unadjusted CH 4 –C 3 H 8 PES with x CH 4 = 0.5.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Relative deviations of experimental data and calculated values for the binary diffusion coefficient of the (CH 4 + C 3 H 8 ) system in the dilute gas phase from values calculated at the same molar densities using the CH 4 –C 3 H 8 PES of the present work, the CH 4 –CH 4 PES of ref , and the C 3 H 8 –C 3 H 8 PES of ref as a function of temperature: ●, Gotoh et al, x CH 4 = 0.5; , Arora et al, x CH 4 = 0.2, smoothed values; – · −, result for the unadjusted CH 4 –C 3 H 8 PES with x CH 4 = 0.5.…”
Section: Resultsmentioning
confidence: 62%
“…Finally, Figures and show the comparison of the calculated values for the product of molar density and binary diffusion coefficient in the dilute gas limit for both systems with the few available experimental data. The binary diffusion coefficient is determined almost entirely by the unlike interactions and, as can be seen in Table , its product with molar density is only very weakly dependent on composition. Therefore, the two figures depict the deviations as a function of temperature instead of mole fraction.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…[9] illustrates deviations of experimental data ( D 12,exp ) (0) of a few authors from theoretical values ( D 12,cal ) (0) computed for the nonspherical potential. Hellmann [9] found that the data of Arora et al [46] given in the temperature range from 275 K to 323 K differ from his calculations only by about −0.5 % , whereas the data of the other authors show deviations > ±1 % . Moreover, Fig.…”
Section: Discussionmentioning
confidence: 76%
“…In previous papers we have reported diffusion coefficients for binary mixtures of argon with nitrogen [t, 2) and oxygen [3,4), and thermal diffusion factors for argon and nitrogen [4,5). The purpose of this paper is to report data for temperature of the diffusion coefficients of the four other binary systems which can be formed from the four major components of air, together with thermal diffusion factors for the systems N 2 -CO 2 and O 2 -CO 2 , Since our method of analysis depends on thermal conductivity measurements, we have been unable to measure useful thermal diffusion factors for the systems Ar -CO 2 and N 2 -O 2 with our present apparatus, however we hope to make modifications which will yield greater sensitivity in the future.…”
Section: Introductionmentioning
confidence: 99%